2018
DOI: 10.1080/02713683.2018.1441873
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Corneal Tomography: Repeatability, Precision, Misalignment, Mean Elevation, and Mean Pachymetry

Abstract: Misalignment limited the repeatability of TMS-5 and Pentacam HR, but had little influence on the repeatability of CASIA SS-1000.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 29 publications
3
45
1
1
Order By: Relevance
“…The calculation of corneal SA requires highest precision of corneal topography in the periphery, since the difference in elevation between an aspheric corneal surface and a spherical surface is only some microns (Figure 4). Schröder et al investigated the measurement repeatability and precision of several corneal topographers and tomographers and found that the repeatability of these devices is decreasing from the center to the periphery and may not be sufficient to detect small changes in corneal asphericity [38].…”
Section: Limitations Of Aberration-correcting Lensesmentioning
confidence: 99%
“…The calculation of corneal SA requires highest precision of corneal topography in the periphery, since the difference in elevation between an aspheric corneal surface and a spherical surface is only some microns (Figure 4). Schröder et al investigated the measurement repeatability and precision of several corneal topographers and tomographers and found that the repeatability of these devices is decreasing from the center to the periphery and may not be sufficient to detect small changes in corneal asphericity [38].…”
Section: Limitations Of Aberration-correcting Lensesmentioning
confidence: 99%
“…In addition, a detailed wavefront parameter analysis with aberration quantification is demonstrated for both anterior and total corneal wavefront. It has been shown that SS-OCT pachymetry results are more repeatable than Scheimpflug imaging results, in healthy corneas [7]. Furthermore, SS-OCT has been shown to have higher reliability and repeatability than high-resolution Scheimpflug imaging in patients who have undergone corneal grafting [8].…”
Section: Ss-oct and Cornea Evaluationmentioning
confidence: 99%
“…Earlier OCT devices were limited by acquisition time and could not perform corneal topography. SS‐OCT has been shown to be more repeatable than Scheimpflug and Placido‐ring devices in keratoconus and following corneal transplantation in measuring keratometry values, elevation, anterior chamber depth and corneal thickness …”
Section: Octmentioning
confidence: 99%